Newborn with Hypoglossia and Micrognathia with Situs Inversus Totalis Born to Mothers with SARS-CoV-2 Infection: A Case Report - Gordana M. Velisavljev-Filipovic; Ognjen Jovanov (Diseases, 2025)
Hypoglossia and micrognathia are rare congenital malformations. They are most likely to occur after disruption of blastogenesis during embryonic development and formation of the first pharyngeal arch. They may be associated with other malformations such as otocephaly or hypogenesis syndrome of the oromandibular limb. We present the case of a female infant with hypoglossia, micrognathia, and situs inversus as a very rare triadic combination. This clinical presentation does not correspond to the description of existing syndromes. In the available literature, we were able to find only a small number of described cases that are somewhat similar to ours. The etiology of hypoglossia with micrognathia and situs inversus is unknown and has been attributed to both genetic and teratogenic causes. It is also unclear whether the combination of these three malformations can be classified as its own syndrome or not. Here, we present a child born from a pregnancy exposed to the SARS-CoV-2 virus in the first weeks of embryonic development, whose whole genome sequencing confirmed normality, as a contribution to elucidating the etiology of these congenital malformations. The possible influence of the SARS-CoV-2 virus on the occurrence of these anomalies and the exact mechanism of action should be confirmed in subsequent research.